Depositors Confidence and Mergers and Acquisitions: The Nigerian Banking Sector Experience - NWAUBANI, Anthony Nzeribe; EZEABASILI, Vincent N (Financial Risk and Management Reviews, 2019)
Nigeria implemented major financial reforms between 2004 and 2005 in which mergers and acquisitions became an imperative option for most of the deposit money banks to meet the new and hiked minimum capital base requirement. This study examined the impact of mergers and acquisitions (M&As) on depositors’ confidence in the Nigerian banking sector. An ex-post facto research design was used with secondary data collected for twenty years. The study covered all the deposit money banks in Nigeria within the period 1995-2015 with 2005 as a base year separating pre and post merger periods. Multiple regression and paired student t-test approaches were employed to analyze the data with the aid of SPSS (20) software. The output yielded mixed findings. While M&As as proxied by dummy merger showed mostly positive and insignificant impact on confidence of depositors, they indicated positive significant impact when measured by shareholders’ funds - an alternate proxy. The paired student t-test yielded significant positive impact on depositors’ confidence. Overall, the findings suggest that the mergers and acquisitions have positively and significantly impacted on depositors’ confidence in the Nigerian banking sector. It is recommended inter-alia that banks should endeavor to further enhance their shareholders’ funds while partnering actively with monetary authorities in pursuit of aggressive financial inclusion via innovative product offerings for cheap deposits and financial stability. This will further enhance the depositors’ confidence in the banking system.